Fertilização nitrogenada e orgânica líquida de pastagens de capim marandu em início de degragação - Freitas, Guilherme Santos (2014)
Nitrogen is a key nutrient for enhancing the productivity of forage grasses , it is the essential constituent of proteins and interfere directly in the photosynthetic process , through its participation in the chlorophyll molecule . Organic matter governed by humic substances its main component , responsible for higher cation exchange capacity of organic origin on the soil surface . The objective of this study was to evaluate some growth rates Brachiaria brizantha . Marandu subjected to nitrogen and humic substances in grasslands with early degradation. Of the nitrogen and humic substances test was performed . The experimental design was in randomized blocks in an experimental arrangement 5x4 , five nitrogen rates ( 0 , 50 , 100 , 200 , 400 kg N / ha ) , four doses of humic substances ( 0 , 12.5, 25 and 50% concentrated material ) with 5 replications. There was significant for doses of N on dry matter yield , plant height , light interception and dry matter production of leaves effect. Doses of humic substances significantly influenced only by reducing the leaf relative / stem. The nitrogen increment the principal indices of Brachiaria brizantha. Doses of humic substances influence only decreasing the leaf / stem ratio of this cultivar